Palatogingival groove: A diagnostic and treatment challenge - Prashanth Prakash; Soumya Raveendran; Ramya Raghu; Keerthi Venkatesan (SRM Journal of Research in Dental Sciences, 2018)
This article presents a case report of a maxillary lateral incisor with a palatogingival groove extending up to the middle third of the root. Despite the poor prognosis, management of the defect was successfully carried out with combined endodontic and periodontal therapy.